A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India - Selvakumar, C.; Subramanian, K. A.; Chandra, Kailash; Jehamalar, E. Eyarin (Zootaxa, 2017)
A new species of Choroterpes Eaton, 1881 is described based on the larvae from India. Choroterpes (Choroterpes) kaegies sp. n. can be distinguished from other known species of the subgenus by the following combination of characters: (i) anteromedian emargination of labrum broad; (ii) each femur with a dark brown spot at middle and near apex; (iii) gill 1 single and slender and (iv) upper and lower lamellae of gills 2–7 with 3 apical processes, median process relatively slender and longer than laterals. A key to the known species of Choroterpes Eaton, 1881 in India is also provided.